USERS’ READINESS EVALUATION IN ADOPTING INTEGRATED INFORMATION SYSTEMS IN THE FINANCE FIELD - Mangaras Yanu Florestiyanto; Wilis Kaswidjanti (Telematika, 2014)
The adoption of Information and Communication Technology (ICT) in the integratedconcept has already became a need to the company or organization that is willing to gaincompetitive advantages as a competitive weapon. However, this adoption is not always smoothbecause of facing challenges. One of the bigest challenge in adopting ICT is the readiness ofICT users. The users’ unreadiness will create resistence toward ICT and further impact will failICT adoption itself. Moreover, it can create inharmony environment in the company ororganization.The purpose of this research is also to evaluate the technology readiness of theusers in the process of adopting ICT in economic field in Finance Directory UGM, estimatedfrom the positive and negative belief of the users toward the technology with adopting methodTRI. The result of this research shows that generally, the readiness of SI users in FinanceDirectory UGM is in medium level, eventhough the users tend to have no comfort feeling andhigh discomfort feeling toward technology users.Keywords: technology readiness, technology adoption